DILEMA ABORSI DALAM TINJAUAN ETIKA ADMINISTRASI PUBLIK - lukman hakim; Putri Retnosari (DIA: Jurnal Administrasi Publik, 2017)
Abortion is the removal of a fetus conceived by a woman with certain actions before her pregnancy complete, either alive or dead before the fetus can live outside the womb. There are many factors that influence an abortion, such as the unfavorable condition of the fetus, sexual behavior outside of marriage, and the result of rape. Various views from religion, law, and health say that abortion is an act that is divided into two, namely; therapeutic abortion provocateurs and abortion provocateurs criminals. The difference is in the handling and awareness of national and state life. This research is a type of qualitative research. Research materials and materials were obtained through library research (library research) related to abortion. Through the implementation of policies and laws that have been made by the government, the public needs to consider the importance of using their public rights which are regulated based on adequate public administration ethics. The government needs to increase professionalism and responsiveness to issues of abortion and unwanted pregnancy. in order to fulfill the overall principle of social justice, by increasing socialization, counseling, and assistance for contraceptives as an initial step in post-abortion prevention and consultation.